The Effect Of Green Accounting And Sales Growth On Cost Control In Manufacturing Companies - Napitupulu, Tri Yohana; Rolyana Ferinia; Valentine Siagian (Universitas Ibn Khladun Bogor, 2024)
This study aims to empirically examine the effect of green accounting and sales growth on cost control. We use the quantitative correlation method to explain how green accounting and sales growth affect cost management in manufacturing companies listed on the IDX from 2021 to 2022, using secondary data. We selected a sample of 53 companies and 106 secondary data points. This study uses logistic regression analysis in data processing. The results showed that (1) green accounting has no effect on cost control, and (2) sales growth has no effect on cost control. These findings suggest that differences in green accounting regulations and practices limit the full optimization of green accounting and sales growth as cost control tools in Indonesia's manufacturing industry.